Pengukuran Kebisingan Pesawat Udara dengan Memasukan Frekuensi Kebisingan di Sekitar Bandara Halim Perdana Kusuma - Raihan Sakti Pratama; Mufti Arifin; Imron Rosadi; Ericko Utama (Jurnal Mahasiswa Dirgantara, 2025)
The high usage of air transportation today is driven by the community's need for faster and more efficient mobility. However, the impact of using aircraft cannot be ignored, especially in terms of noise pollution caused by aircraft engines. Halim Perdana Kusuma Airport, which was originally designed for military activities, has become a commercial airport since 2014 in an effort to reduce flight density at Soekarno-Hatta Airport. This study aims to measure aircraft noise around Halim Perdana Kusuma Airport by including frequency. Measurements were carried out using a dB meter application downloaded on a mobile phone and a Sound Level Meter, both during flight activity and without flight activity in surrounding settlements. The results of this study indicate that noise in dBA can be measured with a Sound Level Meter, while frequency can be measured with a smartphone that has a dB meter application installed. The highest frequency measured during aircraft take-off activity at Halim Perdana Kusuma Airport peaked at 7716 Hz to 7834 Hz, when the noise reached its highest point. From this research, it can be concluded that the higher the frequency The higher the frequency the smaller ∆LA, meaning the dBA is getting closer to the sound pressure level.